Sedentary Behavior and Risk of Depressive Symptoms Among Adolescents in Tianjin: A Cross-Sectional and Longitudinal Analysis of a School-Based Study - De Moraes-Ferrari, G (ELSEVIER, 2026)
Background: Depressive symptoms represent a growing public health concern among adolescents worldwide. While sedentary behavior has been implicated as a contributing factor, longitudinal data from Chinese adolescent populations are still limited. Objectives: To examine the association between sedentary behaviors and the development of depressive symptoms among adolescents in Tianjin, China. Method: A total of 20,738 adolescents aged 12-19 years from the 2022 wave of a school-based survey in Tianjin were included in the cross-sectional analysis. Of these, 4791 participants with available follow-up data collected in 2023 were analyzed prospectively. Self-reported sedentary behavior was categorized into <= 2, 2-4, 4-8, >8 h/ day. Depressive symptoms were assessed on the 20-item Center for Epidemiological Studies Depression Scale (CES-D-20; cutoff score >= 16). We performed multivariable logistic regression models adjusted for demographic, behavioral, and lifestyle factors. Subgroup analyses based on sociodemographic characteristics were also performed. Results: Adolescents engaging in more than 8 h per day of sedentary behavior had greater odds of depressive symptoms in cross-sectional analysis (OR = 1.26, 95 % CI: 1.12-1.42). In prospective analysis, adolescents reporting 4-8 h of sedentary behavior per day showed borderline significance for increased odds of developing depressive symptoms (OR = 1.31, 95 % CI: 0.98-1.75), while those exceeding 8 h demonstrated an elevated risk (OR = 1.67, 95 % CI: 1.23-2.28). No significant interaction by sociodemographic characteristics were detected. Conclusions: Excessive sedentary behavior is longitudinally associated with depressive symptoms among adolescents in Tianjin. These results underscore the need to incorporate strategies aimed at reducing sedentary behavior into early adolescent mental health interventions.
Keywords: Sedentary behavior; Depressive symptoms; Adolescents; China; Longitudinal study; Cross-sectional study